Polyanion sodium cathode material and low temperature water bath preparation method thereof and application in cathode material

The preparation of sodium vanadium fluorogenic sodium phosphate electrode material is solved by low-temperature water bath preparation method, which solves the problems of insufficient tap density and environmental pollution of the existing sodium ion battery positive electrode material, and achieves efficient self-assembly and improves the conductivity of the material.

CN117585661BActive Publication Date: 2025-04-15QINGDAO UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311806228.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-04-15
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have low electronic conductivity and ionic conductivity and insufficient tap density, which limits its industrial application. At the same time, the traditional preparation methods have environmental pollution problems.

Method used

Using a low-temperature water bath preparation method, the mixed solution of sodium, phosphorus and fluorine sources is slowly dripped into the vanadium source solution, the solvent is evaporated in the water bath pot to form a sodium vanadium fluorogenic phosphate electrode material, and finally heated in a tube furnace to obtain the final product.

Benefits of technology

This method effectively improves the tap density and particle size distribution of the material, simplifies the synthesis process, reduces energy consumption, avoids environmental pollution, and improves the self-assembly efficiency and conductivity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117585661B_ABST
    Figure CN117585661B_ABST
Patent Text Reader

Abstract

This application provides a polyanionic sodium cathode material, its low-temperature water bath preparation method, and its application in cathode materials. The preparation method involves: mixing and stirring a sodium source, a phosphorus source, and a fluorine source at a preset temperature to obtain a mixed solution A; dissolving a vanadium source at a preset temperature to obtain a solution B; slowly and uniformly adding mixed solution A to solution B while stirring thoroughly, resulting in a gray flocculent precipitate upon addition, forming a mixture C after addition; placing mixture C in a water bath at a preset temperature and stirring thoroughly until the solution completely changes from gray to cyan-blue; washing the obtained cyan-blue product three times with deionized water and alcohol, drying it, and then heating it in a tube furnace to obtain the final product, sodium vanadium fluorophosphate electrode material. The NVPOF particles obtained by this method have a good particle size distribution, which has a positive effect on subsequent coating and electrode fabrication in the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electrode material preparation, and specifically relates to polyanion sodium positive electrode materials and their low-temperature water bath preparation methods and their applications in positive electrode materials. Background Art

[0002] With the explosive development and widespread popularity of electronic products such as smart phones and electric vehicles, secondary battery technologies such as lead-acid batteries, lithium-ion batteries and sodium-ion batteries have received widespread attention.

[0003] However, due to the relative shortage of lithium ion resources in my country, the lithium resource reserves account for only 7.26% of the world's total, and the resource distribution is extremely uneven. The abundance of sodium in the earth's crust is 2.3%, ranking sixth among all elements, significantly higher than the 0.0017% of lithium. In addition, sodium ion batteries have the advantages of low resource cost, safety and environmental protection, and have broad application prospects in the field of large-scale energy storage. As an important part of sodium ion batteries, positive electrode materials play a decisive role in battery performance and other aspects.

[0004] The cathode materials of sodium ion batteries are mainly composed of layered transition metal oxides, Prussian blue analogs, polyanion compounds, tunnel oxides, and amorphous materials. Among them, NVPOF (NVPF), a material of polyanion compounds, has the advantages of high safety, low cost and environmental friendliness, but its low electronic conductivity and ionic conductivity as well as low tap density limit its practical application in industry.

[0005] At present, the mainstream method is to use the solution gel method (solid phase method) in combination with the spray drying method. With the help of spray drying technology, solutions and emulsions can be directly dried into powder in a short time after atomization to prepare spherical materials and improve the tap density of materials. Its cost is relatively low, time-consuming, and easy to scale up and continuously produce. However, due to the large amount of exhaust gas discharged with dust, special odor and toxic gas components, it will cause serious pollution to the environment. At present, how to improve the tap density of materials through other methods needs further exploration.

[0006] In view of this, this application is hereby filed. Summary of the invention

[0007] In order to solve one of the above technical defects, the embodiments of the present application provide a polyanion sodium cathode material and a low-temperature water bath preparation method thereof and an application in a cathode material.

[0008] According to the first aspect of the embodiment of the present application, a method for preparing a polyanion sodium cathode material is provided, wherein the preparation method adopts a low-temperature water bath; the method comprises the following steps:

[0009] Mixing and stirring a sodium source, a phosphorus source and a fluorine source and dissolving them at a preset temperature to obtain a mixed solution A;

[0010] Dissolving a vanadium source at a preset temperature to obtain a solution B;

[0011] The mixed solution A is slowly dripped into the solution B at a uniform speed, and the mixture is fully stirred while being dripped. A gray flocculent precipitate is generated at the moment of dripping, and a mixture C is formed after the dripping is completed;

[0012] Place the mixture C in a water bath and fully stir and evaporate at a preset temperature until the solution completely changes from gray to cyan blue;

[0013] The cyan-blue product is placed in a tube furnace and heated to obtain the final product, sodium vanadium fluorophosphate electrode material.

[0014] Preferably, the preset temperature is 70°C.

[0015] Preferably, the method specifically comprises the following steps:

[0016] (1) mixing a sodium source, a phosphorus source, and a fluorine source according to a preset ratio, adding deionized water at a preset temperature, stirring according to preset conditions, and obtaining a mixed solution A after the mixture is fully dissolved;

[0017] (2) adding deionized water at a preset temperature to the vanadium source, stirring according to preset conditions, and obtaining a mixed solution B after the vanadium source is fully dissolved;

[0018] (3) adding the mixed solution A to the solution B slowly and evenly, stirring the solution thoroughly during the addition, and producing a gray flocculent precipitate at the moment of the addition, and forming a mixture C after the addition is completed;

[0019] (4) placing the mixture C in a water bath and evaporating it under preset conditions until the solution changes from gray to cyan blue;

[0020] (5) After centrifuging the product of step (4), the product is washed with deionized water and alcohol in turn, the washed product is placed in a drying oven for vacuum drying, and the dried material is ground for later use;

[0021] (6) The ground material is placed in a tubular furnace for calcination, and after natural cooling, sodium vanadium fluorophosphate electrode material is obtained.

[0022] Preferably, the preset condition in step (1) and step (2) is stirring at a rotation speed of 250 r / min for 30 min.

[0023] Preferably, the stirring speed during the sufficient stirring in step (3) is 300 r / min.

[0024] Preferably, the preset conditions in step (4) are: stirring at a speed of 300 r / min in a water bath at a temperature of 70°C.

[0025] Preferably, the vacuum drying conditions in step (5) are: vacuum drying at 80° C. for 12 h.

[0026] Preferably, the tubular furnace calcination conditions in step (6) are: in a pure argon atmosphere, the temperature is increased to 600° C. at a heating rate of 5° C. / min and maintained for 8 h.

[0027] According to the second aspect of the embodiment of the present application, the polyanion sodium positive electrode material is a spherical structure with uniform morphology.

[0028] According to the third aspect of the embodiment of the present application, it includes a polyanion sodium positive electrode material prepared by the above-mentioned preparation method; the positive electrode is composed of the sodium vanadium fluorophosphate electrode material, Super-P and pvdf in a ratio of 8:1:1, the diaphragm is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1MNaClO4, the solvent is a mixture of EC and DEC, and the additive is FEC with a mass fraction of 2%.

[0029] Beneficial effects of this application:

[0030] 1. The present invention converts the solvent from liquid to gaseous state by evaporating the solvent, thereby increasing the concentration of the solute and the contact area between the nanoparticles sodium vanadium fluorophosphate NVPOF. The nanoparticles can be gradually aggregated and arranged in the solution by controlling the solvent volatilization rate and temperature, and finally form a specific spherical structure. In addition, by evaporating and stirring until the color of the solution is completely changed from gray to blue, the required energy can be provided for the self-assembly of the nanoparticles to accelerate the self-assembly process. Under the action of van der Waals forces and non-covalent bonds, particles with uneven surface charge distribution will attract each other. Over time, under this intermolecular interaction, they gradually self-assemble into a uniform spherical structure with a diameter of about 500-1500nm. This method can effectively shorten the reaction time, simplify the synthesis process, and improve production efficiency. It is suitable for large-area self-assembly and structural control, and has certain reference significance for the large-scale preparation of lithium-ion batteries and sodium-ion batteries.

[0031] (2) While the solvent is evaporating, stirring is performed at a certain speed so that the material forms a large-area film on the bottle wall, which greatly improves the evaporation efficiency, shortens the reaction time, and improves the production efficiency. In addition, stirring at a suitable speed can make the nanoparticles of sodium vanadium fluorophosphate NVPOF dissolve and deposit with each other without falling off, and at the same time, more nanoparticles of sodium vanadium fluorophosphate NVPOF can be brought into contact with each other, thereby accelerating the self-assembly process of sodium vanadium fluorophosphate NVPOF. In addition, relative uniformity at the molecular level can be obtained by stirring at a uniform speed, which makes it possible to finally obtain a spherical structure with a size that is close to the same and a uniform morphology. Finally, the purpose of accurately controlling the material morphology and particle size can be achieved by controlling the stirring speed.

[0032] (3) The spherical structure of sodium vanadium fluorophosphate NVPOF synthesized by this method has a particle size of about 500-1500nm, which can be controlled by adjusting the evaporation temperature and stirring rate. The final sodium vanadium fluorophosphate NVPOF particles have a good particle size distribution. The stable spherical structure and good particle size distribution can greatly improve the tap density of the material, which has a positive effect on the subsequent coating and production of electrodes of the battery, can achieve tight stacking, and is conducive to the preparation of high compaction density electrodes, which can effectively improve the energy density of the battery to a great extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0034] Figure 1 This is a SEM image of the sodium vanadium fluorophosphate NVPOF material prepared in the examples of the present application;

[0035] Figure 2 This is the XRD pattern of the sodium vanadium fluorophosphate NVPOF material prepared in the examples of the present application;

[0036] Figure 3 As shown, it is a charge-discharge curve diagram of the sodium vanadium fluorophosphate NVPOF material prepared in the embodiment of the present application at 0.1C;

[0037] Figure 4 This is a rate performance diagram of the sodium vanadium fluorophosphate NVPOF material prepared in the examples of this application;

[0038] Figure 5 This is a cycle performance diagram of the sodium vanadium fluorophosphate NVPOF material prepared in the examples of the present application. DETAILED DESCRIPTION

[0039] In order to make the technical solutions and advantages in the embodiments of the present application more clearly understood, the exemplary embodiments of the present application are further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than an exhaustive list of all the embodiments. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.

[0040] The present application provides a method for preparing a polyanion sodium cathode material, which adopts a low-temperature water bath preparation method; the method comprises the following steps:

[0041] Mixing and stirring a sodium source, a phosphorus source and a fluorine source and dissolving them at a preset temperature to obtain a mixed solution A;

[0042] Dissolving a vanadium source at a preset temperature to obtain a solution B;

[0043] The mixed solution A is slowly dripped into the solution B at a uniform speed, and the mixture is fully stirred while being dripped. A gray flocculent precipitate is generated at the moment of dripping, and a mixture C is formed after the dripping is completed;

[0044] Place the mixture C in a water bath and fully stir and evaporate at a preset temperature until the solution completely changes from gray to cyan blue;

[0045] The cyan-blue product is placed in a tube furnace and heated to obtain the final product, sodium vanadium fluorophosphate electrode material.

[0046] On the basis of the above scheme, the present application provides a method for preparing a polyanion sodium positive electrode material, which specifically includes the following steps:

[0047] (1) Sodium hydroxide, hydrated sodium dihydrogen phosphate, and sodium fluoride are mixed in a beaker in a stoichiometric ratio of 1:8:4, a certain amount of deionized water heated to 70° C. is added thereto, and the mixture is placed on a stirring table and stirred at a speed of 250 r / min for 30 min to fully dissolve the materials, and a mixed solution A is obtained after the materials are fully dissolved;

[0048] (2) Take another beaker, add a mixed vanadium source of ammonium metavanadate and hydrated vanadyl sulfate in the same stoichiometric ratio as the phosphorus source (molar ratio of 2:1), add a certain amount of deionized water heated to 70° C., place it on a stirring table and stir at a speed of 250 r / min for 30 min to fully dissolve the materials, and obtain a mixed solution B after full dissolution;

[0049] (3) Using a burette, the mixed solution A is slowly dripped into the solution B at a uniform speed, and the mixture is fully stirred at a speed of 300 r / min. A gray flocculent precipitate is generated at the moment of dripping, and a mixture C is formed after the dripping is completed;

[0050] (4) placing the mixture C formed in step (3) into a water bath with a preset temperature of 70° C. and stirring at a speed of 300 r / min until the color of the remaining solution in the beaker gradually changes from gray to cyan blue as the solution in the beaker evaporates;

[0051] (5) After centrifugation, the product of step (4) was washed with deionized water three times and with alcohol three times, and the washed product was placed in a drying oven and vacuum dried at 80° C. for 12 h. The dried material was placed in an agate mortar and ground for 30 min for later use;

[0052] (6) The ground material is placed in a tubular furnace for calcination. In a pure argon atmosphere, the temperature is raised to 600°C at a heating rate of 5°C / min and maintained for 8 hours. The purpose is to improve the crystallinity of the material. After natural cooling, a gray-green powdery sodium vanadium fluorophosphate NVPOF electrode material is obtained.

[0053] like Figure 1 As shown, it is a SEM image of the sodium vanadium fluorophosphate NVPOF material prepared in step (6); it can be seen from the figure that the prepared sodium vanadium fluorophosphate NVPOF electrode material is a uniform spherical structure with a particle size of about 500-1500nm.

[0054] like Figure 2 As shown, it is the XRD pattern of the sodium vanadium fluorophosphate NVPOF material prepared in step (6). The data results show that all the diffraction peaks of the NVPOF prepared by this method are well consistent with the tetragonal crystal with space group I4 / mmm (JCPDF No.11-1042), proving that the obtained sample is pure and has no impurity phase. In addition, the NVPOF sample has a large peak value and the prepared NVPOF sample has good crystallinity.

[0055] like Figure 3 As shown in Figure 1, the charge-discharge curve of the sodium vanadium fluorophosphate NVPOF material prepared in step (6) at 0.1C; from the charge-discharge curve of the sample between 2.0-4.3V, two symmetrical working voltage platforms can be observed, which are around 3.6V and 4.0V, respectively, corresponding to the embedding and extraction of Na2 and Na1. The longer the charge-discharge platform, the more Na2 is embedded and extracted. + It provides more capacity, and the discharge specific capacity at 0.1C can reach about 120mAh / g, which is close to the theoretical specific capacity (130mAh / g).

[0056] like Figure 4As shown, the rate characteristics of the electrode of the NVPOF material prepared in step (6) at current densities of 0.1 to 20C are shown. When current densities of 0.1C, 1C, 2C, 5C, 10C, 15, and 20C are applied, the discharge specific capacities of the NVPOF positive electrode are 120mAh / g, 117mAh / g, 110mAh / g, 93mAh / g, 87mAh / g, 78mAh / g, and 70mAh / g, respectively. (Theoretical specific capacity 1C = 130mAh / g), which proves that the sample has good rate performance. When the current returns to 0.1C, there is no significant difference between its specific capacity and the initial capacity, indicating that the material has good stability and reversibility. In addition, the coulomb efficiency of the sample is basically maintained at 100%, indicating that the reaction requires less charge and the current utilization efficiency is high.

[0057] like Figure 5 As shown in FIG. 1 , the NVPOF material prepared in step (6) has a 1C cycle performance diagram. Similar to the rate test results, the sample also has an initial reversible cycle capacity of 117 mAh / g, and the capacity has basically not decayed after 400 cycles at 1C current density, and the capacity retention rate can reach more than 95%, proving that the material has excellent cycle performance and stability.

[0058] In this application, under the action of van der Waals force and non-covalent bond, particles with uneven surface charge distribution will attract each other. Over time, under this intermolecular interaction, they gradually self-assemble into a uniform spherical structure with a diameter of about 500-1500nm. Figure 1 As shown; the present invention increases the contact area between NVPOF particles and the concentration of NVPOF particles in the overall solution by evaporation stirring, accelerates the aging process, and synthesizes the material in a shorter time. In addition, the relative uniformity at the molecular level can be obtained by uniform stirring, so that a spherical structure with nearly uniform size and uniform morphology can be obtained in the end. Figure 1 As shown, the phenomenon of material sinking and aggregation is effectively reduced, which avoids agglomeration and uneven particle size, affecting the final performance of the material.

[0059] In addition, since the particle size distribution range of NVPOF is difficult to control and the tap density is low, the capacity will decay due to the instability of the material during the charge and discharge process. The spherical NVPOF synthesized by this method can accurately control the particle size by adjusting the evaporation temperature and stirring rate. While improving the particle size distribution range and increasing the tap density of the material, it avoids the serious environmental pollution caused by the traditional spray drying granulation method and reduces energy consumption. It is an environmentally friendly synthesis strategy. The synthesized spherical NVPOF particles have a stable structure and can tolerate Na +The volume expansion caused by the charge and discharge process, the spherical material is self-assembled by irregular cubic particles, which increases the specific surface area of ​​the material. There is a certain pore structure on the surface of the material, which is conducive to the full infiltration of the electrolyte, improves the transmission efficiency of sodium ions between the electrode material and the electrolyte, and shortens the Na + Migration paths during charge and discharge, improving ionic conductivity.

[0060] In summary, the method of synthesizing spherical NVPOF cathode materials by low-temperature water bath evaporation has the advantages of being convenient, simple, easy to scale up, and environmentally friendly; Figure 5 As shown in Figure 2, the obtained material has a capacity retention rate of 97.3% at 1C rate after 400 cycles and a capacity of 114 mAh g -1 At a rate of 20C, its capacity can reach 63mAh g -1 , with excellent cycle performance and rate performance.

[0061] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.

Claims

1. A method for preparing a polyanion sodium positive electrode material, characterized in that: A preparation method using a low temperature water bath; Mixing and stirring a sodium source, a phosphorus source and a fluorine source and dissolving them at a preset temperature to obtain a mixed solution A; Dissolving a vanadium source at a preset temperature to obtain a solution B; The mixed solution A is dripped into the solution B at a uniform and slow speed, and the mixture is stirred thoroughly during the dripping. A gray flocculent precipitate is generated at the moment of dripping, and a mixture C is formed after the dripping is completed; Place the mixture C in a water bath and stir it thoroughly at a preset temperature to evaporate until the solution completely changes from gray to cyan blue; stir it at a speed of 300 r / min in a water bath at a temperature of 70°C; The blue product is centrifuged and then washed with deionized water and alcohol in turn, the washed product is placed in a drying oven for vacuum drying, and the dried material is ground for later use; The dried material is placed in a tube furnace and heated to obtain the final product, sodium vanadium fluorophosphate electrode material; The polyanion sodium cathode material is a spherical structure with uniform morphology; the polyanion sodium cathode material is gradually self-assembled into a uniform spherical structure with a diameter of 500-1500nm through intermolecular interaction.

2. The preparation method according to claim 1, characterized in that The preset temperature is 70°C.

3. The preparation method according to claim 1, characterized in that: The specific steps include: (1) Mixing a sodium source, a phosphorus source, and a fluorine source in a preset ratio, adding deionized water at a preset temperature, stirring under preset conditions, and obtaining a mixed solution A after fully dissolving; (2) adding deionized water at a preset temperature to the vanadium source, stirring according to preset conditions, and obtaining a mixed solution B after the vanadium source is fully dissolved; (3) Add the mixed solution A to the solution B slowly and evenly, stirring thoroughly during the addition. A gray flocculent precipitate is produced at the moment of the addition, and a mixture C is formed after the addition is completed. (4) Place mixture C in a water bath and evaporate under preset conditions until the solution changes from completely gray to cyan blue; (5) After centrifuging the product of step (4), the product is washed with deionized water and alcohol in turn, the washed product is placed in a drying oven for vacuum drying, and the dried material is ground for later use; (6) The ground material is placed in a tubular furnace for calcination, and after natural cooling, sodium vanadium fluorophosphate electrode material is obtained.

4. The preparation method according to claim 3, characterized in that: The preset condition in step (1) and step (2) is stirring at a speed of 250 r / min for 30 min.

5. The preparation method according to claim 3, characterized in that: The stirring speed during the thorough stirring in step (3) is 300 r / min.

6. The preparation method according to claim 3, characterized in that: The drying conditions for vacuum drying in step (5) are: vacuum drying at 80° C. for 12 h.

7. The preparation method according to claim 3, characterized in that: The calcination conditions in the tubular furnace in step (6) are: in a pure argon atmosphere, the temperature is increased to 600° C. at a heating rate of 5° C. / min and maintained for 8 h.

8. An application of a polyanion sodium positive electrode material, characterized in that: The invention comprises a sodium vanadium fluorophosphate electrode material prepared by the preparation method as described in any one of claims 1 to 7; the positive electrode is composed of the sodium vanadium fluorophosphate electrode material, Super-P and pvdf in a ratio of 8:1:1, the diaphragm is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1M NaClO4, the solvent is a mixture of EC and DEC, and the additive is FEC with a mass fraction of 2%.

Citation Information

Patent Citations

  • Preparation method of sodium vanadium trifluorophosphate serving as positive electrode material of sodium-ion battery

    CN111606314A